Seeking relational information sources in the digital age: A study into information source preferences amongst family and friends of those with dementia. (April 2020) - Allen, Frances; Cain, Rebecca; Meyer, Caroline
Despite an increasing number of sources providing information and advice about dementia, those living with the condition feel inadequately informed. The reasons for this remain unclear. This study has three aims: to identify where people with dementia and their carers currently access dementia-related information from; to determine how accessible, credible and comprehensible people with dementia and their carers consider the available sources of information; and to determine how people with dementia and their carers would like to receive information. An online or postal survey was completed by 171 female and 41 male participants with a close family member or friend with dementia. Accessibility above quality held the greatest influence over an individual's use of an information source. Participants preferred relational sources such as healthcare professionals as these were able to give individualised information, yet these were poorly accessible and lacked dementia specific knowledge. Therefore, individuals used non-relational sources such as the internet. However, increased use of the internet was linked to feeling overwhelmed by information. It was not the end result of the information search but the effort taken to reach the information that influenced participant's perception of information gathering. Future research should look at ways of designing and providing accessible information sources that act and feel like relational contact.